Sifat–sifat Unggul Morfologis, Fisiologis dan Fenologis Padi Toleran Lingkungan Kering (Review) - GEDE MENAKA ADNYANA (Fakultas Pertanian Universitas Udayana, 2014)
Superior traits of Morphology, Physiology and Phenology of Paddy that Tolerant to Dry-Environment. Ideotype Model of paddy that tolerant to dry environment is a priority for plant breeders to produce varieties that are adapted to dry environments such as rain-fed land. Improvement of crop productivity can be achieved through two approaches, namely environmental improvement and variety improvement. Regarding of variety improvement can also be performed with two approaches i.e conventional and genetic engineering. Through genetic engineering technology, drought resistant cultivars, can be achieved in a relatively short time, and obtained a more varied plant traits. By understanding the mechanisms of plant tolerant to a dry environment, it can be formulated model of superior paddy plants which are adapted to the dry environment. The properties of such tolerance is morphological (root length, root volume, root weight, leaf roll, the wax coating), physiological (decrease transpiration, stomatal closure, accumulation of ABA and proline), and phenological (the elasticity of plant development and the yield stability). The final target is the paddy plant with high yield and stable. This means relatively low yield reduction in dry environmental conditions, compared to the optimal environment.